Internal Audit Quality In North Sumatra Government - Yulisfan; M.Irsan Nasution (International Journal of Management, Economic and Accounting, 2023)
This study explores the concept of internal audit quality within the context of the North Sumatra Government. The focus is on understanding the factors influencing and contributing to the effectiveness and reliability of internal audit practices in the region. Through a quantitative research approach, data is collected to analyze the key components of internal audit quality and their impact on organizational governance. The study employs a survey methodology, distributing questionnaires to internal auditors, management, and other stakeholders involved in the internal audit processes of North Sumatra Government agencies. The research investigates factors such as adherence to professional standards, competency of internal auditors, independence, and the effectiveness of communication within the internal audit function. Preliminary findings indicate a correlation between internal audit quality and the overall governance and risk management framework within the North Sumatra Government. The study contributes to the existing body of knowledge by providing insights into the specific dynamics and challenges faced by internal audit functions in the public sector. The implications of this research extend to government officials, policymakers, and internal audit practitioners, offering recommendations for enhancing internal audit quality to strengthen accountability, transparency, and organizational performance within the North Sumatra Government. The results aim to inform decision-makers and contribute to the continuous improvement of internal audit practices in the regional public sector.